(untitled) (Revista de Medicina Clinica, 2021)
Introduction. Coronavirus Disease 2019 is a multi-systemic disease and the lung is the organ most affected. Pulmonary function tests can help to determine the consequences of this disease. Our objective was to understand the impact of COVID-19 on pulmonary function, functional capacity and health status in a cohort of survivors. Patients and methods. A prospective longitudinal follow-up study of 53 COVID-19 patients was conducted at three and six months after discharge. The assessment included spirometry, lung volumes, pulmonary diffusion capacity, respiratory muscle strength, impulse oscillometry, 6-minute walk test and health-related quality-of-life ShortForm-36 questionnaire. Results. There were 35 male patients (66,0%) with a mean age of 62,77 ± 14,03 years. Almost half of the patients (47,2%) had persistent impaired pulmonary function. The most prevalent impairment was a combination of a restrictive pattern (30,2% of the patients) and an impairment of diffusion capacity (28,3% of the patients). Residual pulmonary function defects were still present at the 6-month evaluation, without significant improvement of lung function over this time, the exception was FVC mean which significantly improved at the 6-month evaluation. Considering the type of ventilatory support, there was no significant differences in lung function parameters, the exceptions were differences between groups regarding Rtot and R5 and R20 parameters. Conclusions. A significant proportion of COVID-19 survivors had impaired pulmonary function at 3-months after discharge and those residual defects were still present at the 6-month evaluation.